2017
DOI: 10.1248/cpb.c16-00798
|View full text |Cite
|
Sign up to set email alerts
|

Guaiane-Type Sesquiterpenoids from Alismatis Rhizoma and Their Anti-inflammatory Activity

Abstract: Twelve guaiane-type sesquiterpenoids, including four new ones, 10-O-methyl-orientalol A (1), 10-Oethyl-alismoxide (2), 3β,4β-expoxy-chrysothol (3), orientalol G (4), and a new norsesquiterpenoid, orientalol H (5), were isolated from Chinese Alismatis Rhizoma, the dried rhizome of Alisma orientale. The structures of new compounds were elucidated on the basis of spectroscopic data. Moreover, the inhibition of lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 cells of all compounds was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Obesity has been proven to be accompanied by inflammation in organs such as the liver and skeletal muscle, consequently promoting metabolic dysfunction and insulin resistance. 37,38 Considering that alisol A has been shown to have antiinflammatory 20 properties, our results also suggested that it could alleviated inflammation in adipose tissue of DIO mice, we supposed that the metabolic improvement effects of alisol A may be partially due to it's suppression of inflammatory damage.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Obesity has been proven to be accompanied by inflammation in organs such as the liver and skeletal muscle, consequently promoting metabolic dysfunction and insulin resistance. 37,38 Considering that alisol A has been shown to have antiinflammatory 20 properties, our results also suggested that it could alleviated inflammation in adipose tissue of DIO mice, we supposed that the metabolic improvement effects of alisol A may be partially due to it's suppression of inflammatory damage.…”
Section: Discussionmentioning
confidence: 69%
“…Modern medical researches about this herb found active ingredients in it and numerous studies have shown that Rhizoma Alismatis extract has various biological activities, such as hypolipemic, antidiabetic, anti‐urinary stone, anti‐inflammation and anti‐tumour activities. Li S et al found that Rhizoma Alismatis extract can significantly reduce the serum LDL levels of ApoE‐/‐ mice and promote the removal of chylomicron in the liver .…”
Section: Introductionmentioning
confidence: 99%
“…Juzepzuk (Alismataceae), is a natural medicine widely cultivated in China, Japan, Korea, India, and Europe. Traditionally, AR is known to exhibit diuretic, hyperlipidemic, inflammatory, antitumoral, and damp-heat clearing actions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] and has been used for treating dysuria, edema, urinary tract infection, retention of fluid and phlegm, and vertigo for more than 1000 years [ 8 ]. As a folk medicine that has long been used to promote health and longevity, AR is now included in the Pharmacopoeia of China as a representative traditional Chinese herbal diuretic.…”
Section: Introductionmentioning
confidence: 99%
“…S. Kitam flowers. And pharmacological investigations showed that this kind of compounds exhibited mainly cytotoxicity and anti-inflammatory activities [15][16][17] ; however, there has been no research about the mechanism. We investigated the protective effects of guaianetype sesquiterpenoids on LPS-induced injury in H9c2 cardiomyocyte in order to find the mechanism and the effective drugs to protect cardiomyocyte injury in our study.…”
Section: Discussionmentioning
confidence: 99%